Foraging investment in a long‐lived herbivore and vulnerability to coursing and stalking predators. Issue 20 (17th September 2018) - Christianson, David; Becker, Matthew S.; Brennan, Angela; Creel, Scott; Dröge, Egil; M'soka, Jassiel; Mukula, Teddy; Schuette, Paul; Smit, Daan; Watson, Fred
Abstract: Allocating resources to growth and reproduction requires grazers to invest time in foraging, but foraging promotes dental senescence and constrains expression of proactive antipredator behaviors such as vigilance. We explored the relationship between carnivore prey selection and prey foraging effort using incisors collected from the kills of coursing and stalking carnivores. We predicted that prey investing less effort in foraging would be killed more frequently by coursers, predators that often exploit physical deficiencies. However, such prey could expect delayed dental senescence. We predicted that individuals investing more effort in foraging would be killed more frequently by stalkers, predators that often exploit behavioral vulnerabilities. Further these prey could expect earlier dental senescence. We tested these predictions by comparing variation in age‐corrected tooth wear, a proxy of cumulative foraging effort, in adult (3.4–11.9 years) wildebeest killed by coursing and stalking carnivores. Predator type was a strong predictor of age‐corrected tooth wear within each gender. We found greater foraging effort and earlier expected dental senescence, equivalent to 2.6 additional years of foraging, in female wildebeest killed by stalkers than in females killed by coursers. However, male wildebeest showed the opposite pattern with the equivalent of 2.4 years of additional tooth wear in males killed by coursers as compared to those killed by stalkers. Sex‐specific variation in the effects of foraging effort on vulnerability was unexpected and suggests that behavioral and physical aspects of vulnerability may not be subject to the same selective pressures across genders in multipredator landscapes. Abstract : Foraging is necessary for herbivores to grow and reproduce, but foraging also causes tooth erosion, which shortens life span. How herbivores negotiate this trade‐off has been primarily explored in systems without large predators. When selecting prey, coursing and stalking carnivores exploit unique vulnerabilities that might arise from variable expression of the "grow fast, die young" trade‐off. Female wildebeest killed by coursing carnivores foraged much less than those killed by coursers, but the exact opposite pattern was observed in male wildebeest.